Differences in The Effectiveness of Buerger Allen Exercise and Foot Exercises on Peripheral Perfusion in Type 2 Diabetes Mellitus - Jannah, Rofiatul; Fatarona, Anita; Cahyono, Hendra Dwi (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2024)
Diabetes mellitus results in both microvascular and macrovascular complications due to inadequately managed glucose levels over an extended period. A notable complication is peripheral neuropathy, which arises from compromised peripheral circulation. Implementing Buerger Allen Exercises and Foot Exercises can enhance circulation and mitigate these complications, with effectiveness assessed using the ankle-brachial index. This study aims to evaluate the differential efficacy of Buerger Allen Exercises compared to Foot Exercises in improving peripheral perfusion among patients diagnosed with type 2 diabetes mellitus affiliated with the Patrang Community Health Center. The research employs a quasi-experimental design featuring a pretest-posttest two-group format. The study sample consists of 30 respondents diagnosed with type 2 diabetes mellitus. The intervention, which included both Buerger Allen Exercises and Foot Exercises, was conducted once and lasted 20 minutes. The results indicate that the Buerger Allen Exercise group exhibited an average ankle-brachial index value of 0.992, while the Foot Exercise group yielded an average value of 0.900. The obtained p-value (0.004) was less than or equal to the alpha level of 0.005. Therefore, a statistically significant difference exists between the Buerger Allen Exercise intervention group and the Foot Exercise group. In conclusion, the Buerger Allen Exercise intervention is more effective than the Foot Exercise regimen in enhancing peripheral perfusion, as evidenced by the measured ankle-brachial index values.